A distance measurement method based on binocular vision for underwater target - Yang Ge; Wang Zhenyao (Dianzi Jishu Yingyong)
Based on the high sensitivity, low cost and easy portability of underwater robot for ocean detection, this paper studies the key binocular vision detection technology applied to the ranging of underwater target objects. Zhang Zhengyou′s calibration algorithm was adopted to obtain the parameters of the internal and external matrix model of the underwater binocular camera by using a 9×9 checkerboard, and SGBM stereo matching algorithm was adopted to enhance the image contrast and weaken the influence of image color spots. It ensures the robustness of the algorithm, improves the matching search speed, transforms the parallax map into depth map through matrix operation, and maps it into visual point cloud to construct the three-dimensional information of the target object.